Contribution of Archbishop Volodymyr Sternyuk to the Evolution of the Underground Ukrainian Greek Catholic Church - Mariya Kokhanovska (Codrul Cosminului, 2018)
This article analyses Archbishop Volodymyr Sternyuk’s role in the history of the Ukrainian Greek Catholic Church (UGCC). It explores the scientific and spiritual development of Volodymyr Sternyuk and his contacts with prominent personalities during his time as Church leader when the Church itself was abolished by the Soviet authorities. It examines his methods of pastoral and administrative work in the time when UGCC was restricted. The essay illustrates the interconnection of religious and national factors in Volodymyr Sternyuk’s life. Research is based on interviews of parishioners and clergy close to Volodymyr Sternyuk as well as his own recollections.